Du dessin à la restitution virtuelle, l’utilisation des nouvelles technologies dans l’étude de la sculpture du haut Moyen Âge - Jessy Crochat; Anne Flammin (Les Cahiers de l'École du Louvre)
Although manual surveying is still the most relevant tool for the study of sculpture, archaeologists have recently started using new technologies such as photogrammetry, lasergrammetry and reflectance transformation imaging (RTI). The scatter charts generated constitute digital prints from which cross-sections, profiles and orthophotographs may be extracted. It is possible to restore missing parts of the sculptures and to create assemblages that are often impossible to implement otherwise. The virtual model also makes it possible to test hypotheses. We will thus study the advantages and disadvantages of these new digital surveys using various examples, most of which come from our own work.